2000
DOI: 10.1046/j.1365-2648.2000.01516.x
|View full text |Cite
|
Sign up to set email alerts
|

Who cares? Offering emotion work as a ‘gift’ in the nursing labour process

Abstract: Who cares? Offering emotion work as a 'gift' in the nursing labour process The emotional elements of the nursing labour process are being recognized increasingly. Many commentators stress that nurses' 'emotional labour' is hard and productive work and should be valued in the same way as physical or technical labour. However, the term 'emotional labour' fails to conceptualize the many occasions when nurses not only work hard on their emotions in order to present the detached face of a professional carer, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
277
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(297 citation statements)
references
References 21 publications
13
277
1
4
Order By: Relevance
“…Nurses' motivation could be deeply connected with the meaning that they give to their work and with certain job demands from the health field (Edgar, 1998). These demands are in many cases the relationships with patients which can be perceived by nurses like a "gift" (Bolton, 2000). In their study among student nurses, McCabe et al (2005), found that the most important reasons to choose the profession were (1) to help others; (2) to do interesting and challenging work; and (3) to work closely with people in need.…”
Section: Emotional Demands Motivation and Well-being In Nursing Profmentioning
confidence: 99%
“…Nurses' motivation could be deeply connected with the meaning that they give to their work and with certain job demands from the health field (Edgar, 1998). These demands are in many cases the relationships with patients which can be perceived by nurses like a "gift" (Bolton, 2000). In their study among student nurses, McCabe et al (2005), found that the most important reasons to choose the profession were (1) to help others; (2) to do interesting and challenging work; and (3) to work closely with people in need.…”
Section: Emotional Demands Motivation and Well-being In Nursing Profmentioning
confidence: 99%
“…They have shown that controlling one's emotions is central to caring jobs such as nursing and midwifery. A competent practitioner is able to carry out the work without becoming too emotionally involved with the patients, to uphold a professional approach and to support patients (see Bolton 2000;Fineman 2005;Hunter 2001;James 1992;Smith 1998). In her study of gynecology nurses, Sharon C. Bolton sees their work as "maintaining the professional face" which means that they learn to "mask" their own feelings in order to be able to emotionally support the patients (2000: 584).…”
Section: Norms About Feelings and Emotionsmentioning
confidence: 99%
“…Bolton 2000, Fineman 2005, Hunter 2001, Sturdy 2003, Thoits 1989. They have shown that controlling one's emotions is central to caring jobs such as nursing and midwifery.…”
Section: Norms About Feelings and Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have explored the emotional component of public sector "care workers" including nurses (Smith 1992, James 1993, Bolton 2000, the complex relationships between individual practitioners and organisations associated with the development of new nursing roles (Franks and Smith, 2002)) social workers (Aldridge 1994) and midwives (Hunter 2004). Few studies have described the emotional labour associated with inner city regeneration work and the conditions required to sustain it (see for example Froggett and Chamberlayne 2004).…”
Section: Introductionmentioning
confidence: 99%